Społeczno-kulturowe ramy pamięci w działaniach Towarzystwa Gimnastycznego „Sokół” na terenie Niemiec przełomu XIX i XX wieku - Piotrowska, Magdalena; Molenda, Piotr (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article offers a new perspective on the role of the Sok.ł Gymnastic Society in the circles of Polish immigrants in Germany at the turn of the 20th century, presenting examples of Sok.ł’s activity in numerous places (including Berlin, Leipzig, Bochum) and the variety of forms of presentation used (poetry – song – drama; cultural performances). The theoretical considerations are preceded by a brief discussion of the history of the movement, with particular emphasis on the specificity of Sok.ł’s activities in the areas under Prussian rule. The use of new methodologies and studies of cultural memory and the categories of myth made it possible to reconstruct the social and cultural framework of memory. The analysis may be an incentive to revise the common views, allowing one to ask questions about the place and the role of collective memory, about the media of memory or the meaning of the phonic space.